Pollen Morphology of Stachys L. Spp. Growing in Iraq - A.Al-Bayati, M.KH (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present work included new information about pollen of eighteen Spp. of Stachys  L. in Iraq ;showed their importance in diagnostsis.Pollen shapes in equatorial view were ellipsoid in most spp .and spherical - subspherical ,  spherical - subprolate and  subprolate -ellipsoid in others; while they were spherical - subspherical in polarview . Pollen was tricolpate except St.iberica  M.B.georgica Rech.f. &Ten. Which has tetracolpate and that was new for the genus.The smallest pollen were seen in St.kotschyi  Boiss. & Hohen. but the biggest were in St.benthamiana Boiss.